2014
DOI: 10.1007/s40140-014-0061-x
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of EEG-Based Depth-of-Consciousness Monitoring During General Anesthesia

Abstract: Monitoring the level of consciousness during general anesthesia with processed electroencephalogram (EEG) monitors has become an almost routine practice in the operating room, despite ambiguous research results regarding its potential benefits. For the patient as well as the anesthesiologist, the primary concern with respect to general anesthesia is that there will be a lack of awareness and recall during surgery. Using EEG signals to monitor the depth of anesthesia should reduce the incidence of intraoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 71 publications
0
22
0
2
Order By: Relevance
“…It was previously thought that unconsciousness and amnesia during general anesthesia were brain cortical phenomena [4]. However, according to the study of Långsjö et al [33], subcortical structures of the brain are also involved during the emergence of consciousness during anesthesia.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It was previously thought that unconsciousness and amnesia during general anesthesia were brain cortical phenomena [4]. However, according to the study of Långsjö et al [33], subcortical structures of the brain are also involved during the emergence of consciousness during anesthesia.…”
Section: Discussionmentioning
confidence: 97%
“…SE parameter of spectral entropy is delivered from frontal EEG and this may be the reason why no changes in the SE value were seen during arousal i.e., this parameter does not monitor activity in subcortical brain structures. This can be considered as a limitation of EEG based anesthesia monitoring since it only registers the cortical frontal EEG [4]. However, frontal muscles activation, measured by RE parameter, may indicate inadequate subcortical component of anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When BIS is over 60, there is the possibility of awareness risk during general anesthesia. BIS monitoring has been reported to reduce the risk of intraoperative awareness in populations at high risk 6,7 . A previous study reported that for patients receiving 4 mg/ kg of thiopental, the BIS value is >60 at the time of incision 8 .…”
Section: Comparison Of Electroencephalogram Between Propofol-and Thiomentioning
confidence: 99%
“…All patients were ventilated with 100% oxygen for a few minutes before and after RVP periods. Anesthesia was maintained with an infusion (2 -8 mg/kg/h) of propofol aiming at a state entropy of under 60 [19].…”
Section: Anesthesia and Hemodynamic Managementmentioning
confidence: 99%